Cellular and molecular mechanisms of neuronal pruning in dendrite arborization neurons. - Zhou, Zimin. (2011)
Pruning, which selectively eliminates superfluous neuronal processes without causing neuronal death, is an important process of neuronal remodeling during development. Here in the first part of this study, we report the results of a genome-wide RNA interference screen in Drosophila melanogaster class IV dendritic arborization neurons (ddaC) for novel genes that are involved in dendrite pruning. We identified four novel genes: Nmnat (Nicotinamide mononucleotide adenylyltransferase); Snap (Soluble NSF attachment protein); Ank2 (Ankyrin 2); Msps (Mini Spindles). Knocking-down these four genes by RNAi result in dendrite pruning defects in ddaC neurons at 16h after puparium formation (16h APF). In the second part of this study, we used double RNAi screen to identify other molecules that may be related to Mical (Molecule interacting with casL) during pruning process. We isolated 12 genes that may function parallel to or synergistically with Mical, as well as one gene called Unc-115 (Uncoordinated 115) that may operate in the same genetic pathway with Mical. Therefore, our findings have enlarged the number of known genes that affect pruning process and will provide insights into cellular and molecular mechanisms of neuronal pruning.